Utilization of Wordwall as an Interactive Game Media to Improve Motivation and Learning Outcomes of Asmaul Husana of Elementary School Students - Suwanto Suwanto (FITK UIN Walisongo Semarang, 2025)
Monotonous and less interactive learning often leads to a decrease in student motivation and learning outcomes, especially in memorized subjects such as Islamic Religious Education (PAI). This study aims to analyze efforts to improve the learning outcomes of grade V students in Asmaul Husna's material through the application of Wordwall interactive game media. The research uses a classroom action research (PTK) approach with a spiral design consisting of two cycles, involving 28 students of SDN Nongkosawit 01 as subjects. Data collection is carried out through observation, questionnaires, and documentation of learning outcomes, while data analysis is descriptive, qualitative, and quantitative. The results showed a significant increase in learning completion: in the pre-cycle only 35.71% of students completed (average class 63.17), increased to 57.14% in cycle I (average 68.00), and reached 84.21% in cycle II (average 74.64). These findings prove that the use of Wordwall interactive game media is effective in improving students' understanding and learning outcomes in Asmaul Husna's material. The implications of this research provide practical contributions for teachers in designing innovative, interactive, and fun learning, while enriching the treasures of technology-based learning media development in elementary schools.